2018
DOI: 10.3390/su10114257
|View full text |Cite
|
Sign up to set email alerts
|

A Bi-Objective Vehicle-Routing Problem with Soft Time Windows and Multiple Depots to Minimize the Total Energy Consumption and Customer Dissatisfaction

Abstract: In recent years, the impact of the energy crisis and environment pollution on quality of life has forced industry to actively participate in the development of a sustainable society. Simultaneously, customer satisfaction improvement has always been a goal of businesses. It is recognized that efficient technologies and advanced methods can help transportation companies find a better balance between progress in energy saving and customer satisfaction. This paper investigates a bi-objective vehicle-routing proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In this study, emphasis will be placed on the OFs focusing on the environmental, social and economic contexts, reverse logistics, fuel consumption and CO 2 emissions. Thus, it can be said that many authors are concerned with minimizing costs, be they operational, general, financial or for transport (Abad et al, 2018;Govindan et al, 2017;S. Wang et al, 2018b) or maximizing revenues or profit (Niknamfar & Niaki, 2016;Zohal & Soleimani, 2016), as well as minimizing the number of vehicles (Y. Guo et al, 2017; Y.…”
Section: Vrp With Environmental Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, emphasis will be placed on the OFs focusing on the environmental, social and economic contexts, reverse logistics, fuel consumption and CO 2 emissions. Thus, it can be said that many authors are concerned with minimizing costs, be they operational, general, financial or for transport (Abad et al, 2018;Govindan et al, 2017;S. Wang et al, 2018b) or maximizing revenues or profit (Niknamfar & Niaki, 2016;Zohal & Soleimani, 2016), as well as minimizing the number of vehicles (Y. Guo et al, 2017; Y.…”
Section: Vrp With Environmental Considerationsmentioning
confidence: 99%
“…Figure 5(a) shows the relationship between the taxonomies of the VRP with Environmental Considerations presented here. We can observe (yellow circle on the left) that 12 articles in the sample address the MOO-GVRP(Abad et al, 2018;Androutsopoulos & Zografos, 2017; Coelho et al, 2017; Demir et al, 2014b; Hassanzadeh & Rasti-Barzoki, 2017;Norouzi et al, 2017;Poonthalir & Nadarajan, 2018;Psychas et al, 2016;Rani & Reddy, 2017;Rao et al, 2016;Rau et al, 2018;S. Wang et al, 2018b).…”
mentioning
confidence: 92%
“…NSGA-II and multi-objective particle swarm optimization (MOPSO) were adopted to solve the problem, and the MOPSO was found to outperform the NSGA-II. Wang et al (2018) studied a bi-objective vehicle-routing problem with soft time windows and multiple depots, and the goal was to simultaneously minimize total energy consumption and customer dissatisfaction. An MIP model was first developed, and an augmented e-constraint method was applied to obtain the optimal Pareto front for small problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The numerical examples showed that the proposed approach is useful in determining the optimal compromise between travel time increase and energy decrease. Wang et al [15] investigated a multi-objective vehicle-routing optimization problem, where the objectives aimed to minimize total energy consumption and customer dissatisfaction, simultaneously. The study found a better balance between energy consumption diminishment and customer satisfaction and, finally, developed a mixed integer programming model to address the problem.…”
Section: Literature Reviewmentioning
confidence: 99%